Interactional justice, leader–member exchange, and employee performance: Examining the moderating role of justice differentiation. (1st September 2016) - He, Wei; Fehr, Ryan; Yam, Kai Chi; Long, Li‐Rong; Hao, Po
Summary: Past research suggests that interactional justice plays a pivotal role in facilitating high‐quality leader–member exchange (LMX), with downstream implications for employee performance. However, the broader context in which these effects unfold has received scarce attention. Drawing from deontic justice and social exchange theories, we suggest that interactional justice differentiation is an important contextual moderator of the link between interactional justice and LMX. Specifically, we argue that high interactional justice differentiation attenuates the link between interactional justice and LMX, in turn influencing the effects of interactional justice on employee task and creative performance. Results from two studies employing both experimental and multisource, multilevel survey designs provide convergent support for the hypothesized model. We conclude by highlighting several key theoretical and practical implications of our findings. Copyright © 2016 John Wiley & Sons, Ltd.